The effect of elastic stockings and leg elevation on the prevention of hypotension during plasmapheresis - Khodayar Oshvandi; Armin Mohamadiparsa; Zahra Khalili; Leili Tapak; Massoud Ghiasian (حیات)
Background & Aim: Hypotension is a common complication associated with plasmapheresis. Elevating the legs and using elastic stockings are nursing interventions aimed at preventing hypotension. The objective of this study was to compare the effects of elastic stockings and leg elevation on the prevention of hypotension during plasmapheresis. Methods & Materials: This randomized crossover clinical trial was conducted on 35 patients undergoing plasmapheresis at Beheshti Hospital in Hamadan from 2020 to 2021. Patients were selected based on convenience sampling and then allocated to four different methods in four sessions using random permuted block designs: elastic stockings (A), leg elevation (B), a combination of elastic stockings and leg elevation (C), and a control group (D). Blood pressure was monitored before, during (every half hour), and half an hour after the completion of plasmapheresis. Data analysis was performed using SPSS version 24, applying repeated measures ANOVA with a significance level of 0.05. Results: During plasmapheresis, systolic blood pressure decreased over time in all four methods (P<0.001). Blood pressure measurements in intervention methods A, B, and C were higher than in the control group (P<0.001). Among the intervention methods, blood pressure in method C was higher than in methods A and B, while method B was higher than method A (P<0.001). Conclusion: The use of elastic stockings in combination with leg elevation is more effective in preventing hypotension. Therefore, it is recommended as an easy and cost-effective method for preventing hypotension in patients undergoing plasmapheresis and for nursing staff to implement. Clinical trial registry: IRCT20191020045166N1